Perencanaan Kegiatan Tahsin Qiraatil Quran dalam Program Tadarus AlQuran Untuk Guru di SMP N 13 Kota Padang - Afdryan Ramatdany; Indah Muliati (ISLAMIKA, 2022)
This study was motivated by the policy of the headmaster of Sekolah Menengah Pertama Negeri 13 Padang City requiring teachers to come to school during the Covid-19, then in the morning filled with tahsin qiraatil Quran activities in the tadarus Quran program for teachers of SMP N 13 Padang City. This Study uses a qualitative method with a case study approach. Sources of data were taken from five informants through in-depth interviews which were selected using the purposive sampling technique. The five informants consisted one of Headmaster Sekolah Menengah Pertama Negeri 13 Padang City, two mentors, and two participants in the activity. To obtain the results of interviews, this study used an interview protocol as a research instrument. Data collection techniques used are observation, interviews, and documentation. While the data analysis techniques that the author uses are data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the planning of Tahsin Qiraatil Quran Activities in the Tadarus Quran Program for Teachers found four things needed; a) determining mentors, b) making lesson plans, c) preparing supporting media, d) determining participants, methods, and places of activities.